Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations - Meshram, Naresh M.; Rai, Stuti; Rajgopal, N. N.; Ramya, N. (Zootaxa, 2018)
Two new species of leafhoppers, Durgades sineprocessus sp. nov. (From Himachal Pradesh: Kalpa) and Japanagallia dolabra sp. nov. (From Sikkim: Lachung) from India, are described and illustrated. Photographic illustrations of Durgades aviana Viraktamath and a detailed note on intraspecific variation in male genitalia of Austroagallia sinuata (Mulsant & Rey) are also provided. Material is deposited in the National Pusa Collection, Division of Entomology, Indian Council of Agricultural Research-Indian Agricultural Research Institute (ICAR-IARI), New Delhi, India.